58. KNOWLEDGE AND PRACTICES ON DENGUE HEMORRHAGIC FEVER (DHF) PREVENTION AND CONTROL AMONG RESIDENTS IN THU DAU MOT CITY, BINH DUONG PROVINCE IN 2025, AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the current status of knowledge and practices regarding Dengue hemorrhagic fever prevention and control among residents in Thu Dau Mot city, Binh Duong province in 2025, and to analyze related factors. Thereby recommending that local authorities implement effective intervention measures.Methods: A descriptive cross-sectional study was conducted involving 352 household heads or representatives aged 18 years and older, residing in three wards including Hiep Thanh, Phu Cuong, and Phu Tho of Thu Dau Mot city. Data were collected using structured interviews with a questionnaire and direct household observations using a standardized supervision checklist.Results: The proportion of residents with adequate knowledge and appropriate practices regarding Dengue hemorrhagic fever prevention was 65.9% and 69.3%, respectively. Occupational status was significantly related to overall knowledge (p < 0.05). Educational level, household economic status, and the number of Dengue hemorrhagic fever-related information sources accessed were significantly related to overall preventive practices (p < 0.05).Conclusion: The level of knowledge and appropriate practices for Dengue hemorrhagic fever prevention among residents in Thu Dau Mot city in 2025 remains suboptimal. Enhanced intersectoral collaboration is necessary from the provincial Department of Health to local authorities for budget allocation, strategic planning, training, communication, and supervision of Dengue hemorrhagic fever prevention programs. Furthermore, community organizations, mass associations, and residents must actively engage in environmental sanitation, mosquito breeding site elimination, and community-based disease prevention efforts.
Keywords: Dengue hemorrhagic fever; knowledge; practices; Thu Dau Mot.